Accelerated Transfer and Spillover of Carbon Monoxide through Tandem Catalysis for Kinetics‐boosted Ethylene Electrosynthesis. Issue 10 (25th January 2023) - Chen, Jiayi; Wang, Dashuai; Yang, Xiaoxuan; Cui, Wenjun; Sang, Xiahan; Zhao, Zilin; Wang, Liguang; Li, Zhongjian; Yang, Bin; Lei, Lecheng; Zheng, Jinyang; Dai, Liming; et al.
Abstract: Cu‐based catalysts have been widely applied in electroreduction of carbon dioxide (CO2 ER) to produce multicarbon (C2+ ) feedstocks (e.g., C2 H4 ). However, the high energy barriers for CO2 activation on the Cu surface is a challenge for a high catalytic efficiency and product selectivity. Herein, we developed an in situ *CO generation and spillover strategy by engineering single Ni atoms on a pyridinic N‐enriched carbon support with a sodalite (SOD) topology (Ni‐SOD/NC) that acted as a donor to feed adjacent Cu nanoparticles (NPs) with *CO intermediate. As a result, a high C2 H4 selectivity of 62.5 % and an industrial‐level current density of 160 mA cm −2 at a low potential of −0.72 V were achieved. Our studies revealed that the isolated NiN3 active sites with adjacent pyridinic N species facilitated the *CO desorption and the massive *CO intermediate released from Ni‐SOD/NC then overflowed to Cu NPs surface to enrich the *CO coverage for improving the selectivity of CO2 ER to C2 H4 . Abstract : A unique *CO transfer and spillover strategy was developed by fabricating Ni single atom supported on pyridinic N‐enriched carbon as a *CO donor for feeding Cu NPs with *CO, boosting the coverage of *CO on Cu NPs and subsequently improving the selectivity for CO2 ‐C2 H4 conversion.